The clinical and economic burden of systemic sclerosis related interstitial lung disease. (18th November 2019) - Morrisroe, Kathleen; Stevens, Wendy; Sahhar, Joanne; Ngian, Gene-Siew; Ferdowsi, Nava; Hansen, Dylan; Patel, Shreeya; Hill, Catherine L; Roddy, Janet; Walker, Jennifer; Proudman, Susanna; Nikpour, Mandana
Abstract: Objective: To quantify the burden of interstitial lung disease (ILD) in SSc. Methods: Clinical data for SSc patients enrolled in the Australian Scleroderma Cohort Study were linked with healthcare databases for the period 2008–2015. ILD was defined by characteristic fibrotic changes on high-resolution CT (HRCT) lung, while severity was defined by the extent lung involvement on HRCT (mild <10%, moderate 10–30%, severe >30%). Determinants of healthcare cost were estimated using logistic regression. Results: SSc-ILD patients utilized more healthcare resources, including hospitalization, emergency department presentation and ambulatory care services, than those without ILD with a total cost per patient of AUD48 368 (26 230–93 615) vs AUD33 657 (15 144–66 905), P <0.001) between 2008–2015. Healthcare utilization was associated with an annual median (25th–75th) excess cost per SSc-ILD patient compared with those without ILD of AUD1192 (807–1212), P <0.001. Increasing ILD severity was associated with significantly more healthcare utilization and costs with an annual excess cost per patient with severe ILD compared with mild ILD of AUD2321 (645–1846), P <0.001. ILD severity and the presence of coexistent PAH were the main determinants of overall healthcare cost above median for this SSc-ILD cohort (OR 5.1, P <0.001, and OR 2.6, P =0.01, respectively). Furthermore, SSc-ILD patients reported worse physical HRQoL compared with those without ILD [34.3 (10.5) vs 39.1 (10.8), P <0.001], with a progressive decline with increasing ILD severity ( P =0.002). Conclusion: SSc-ILD places a large burden on the healthcare system and the patient through poor HRQoL in addition to incremental healthcare resource utilization and associated direct cost.